REGULASI CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP LINGKUNGAN HIDUP DALAM HUKUM INDONESIA - Kadek Ary Purnama Dewi (Jurnal Yustitia, 2018)
Corporate social responsibility (CSR) is one part of implementing business ethics in running a company. CSR is a form of corporate responsibility towards the surrounding environment and to all stakeholders, including employees, consumers, shareholders and the environment itself in the operational aspects of the company. In this study, the regulation of CSR on the environment in Indonesian law will discuss the legal obligations of CSR for the environmentand CSR arrangements in the future legislation. The obligation to implement CSR on the environment is regulated in a number of laws and regulations in Indonesia, namely Law Number 40 of 2007 concerning Limited Liability Companies, Law Number 25 of 2007 concerning Investment, and Law Number 21 of 2014 concerning Geothermal. Regulations regarding CSR are only a small part of the normative formula in legislation, consequently the implementation of CSR can be ignored by the company. In future arrangements, provisions regarding CSR need to be made in one law.